Theory for deformation of laminate with multiple inhomogeneous inclusions. (January 2022) - Higuchi, Ryo; Hayashi, Ibuki; Yokozeki, Tomohiro; Aoki, Takahira
Abstract: This study proposes a theory for predicting the deformation of laminates embedded or mounted with multiple inhomogeneous inclusions. A particular example of the latter is an ultra-thin planar antenna with a large number of antenna patches for satellites or a solar sail panel with several actuators. The thermal or piezoelectric strains of patches and actuators in these structures can be regarded as a problem of generalized eigenstrain, which comprises in-plane eigenstrain and eigencurvature. In this study, Eshelby's equivalent inclusion method in the framework of classical lamination theory (CLT) is employed to consider the effect of a single inhomogeneous inclusion in/on the laminate. Furthermore, Mori–Tanaka's mean-field method was extended to the CLT to deal with interactions between multiple inhomogeneous inclusions. Combining these two methods allows the deformation of laminates with multiple inhomogeneous inclusions to be predicted. The proposed method is verified against finite element analysis in a simple two-layer problem comprising an infinite or finite plate mounted by multiple inhomogeneous inclusions.